THE EFFECT OF PRE-OPERATION BASED EDUCATION ON ANXIETY REDUCTION AMONG PATIENTS WITH POST OPEN REDUCTION INTERNAL FIXATION - Firman Oswari; Dwikora Novembri Utomo; Ninuk Dian Kurniawati (International Journal of Nursing and Health Services (IJNHS), 2019)
Open Reduction Internal Fixation (ORIF) is one of the management among patients who have a fracture. The study aimed at examining the effect of health education pre-operation anxiety reduction among fracturing patients cruris post open reduction internal fixation. A quasi-experimental, pre-test and post-test with non-equivalent control group was applied in this study. Thirty-four samples were recruited by using total sampling and divided into two intervention and control groups. Data analysis was performed and presented in descriptive statistics, and significant findings were computed using the paired t-test. Results: The results showed that the mean anxious level intervention group downhill from 28,76+4,603 to 16,61+2,487 after the intervention. Meanwhile, in the control group, the mean anxious level slightly downhill from 28,18+4,066 to 23,82+4,362. The paired t-test obtained a p-value of 0.000, indicating that there were significant differences in the decrease in anxiety level between the intervention and the control group. Conclusion: Preoperative health education interventions based on the health belief model can reduce the level of anxiety in patients with cruris fractures after ORIF surgery. The nurse profession is expected to be able to use preoperative health education actions based on the health belief model to become one of the independent nursing interventions. Keywords: pre-operation based education, fracture, anxiety reduction